2020
DOI: 10.2139/ssrn.3600806
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity and Fairness in Times of Crisis

Abstract: In a large-scale pre-registered survey experiment with a representative sample of more than 8,000 Americans, we examine how the COVID-19 pandemic causally affects people's solidarity and fairness. We randomly manipulate whether respondents are asked general questions about the crisis before answering moral questions. By making the pandemic particularly salient for treated respondents, we causally identify how the crisis changes moral views. We find that the crisis makes respondents more willing to prioritize s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
2
19
1
Order By: Relevance
“…Interestingly, recent studies in adults have suggested that during the pandemic there is a shift towards pandemic-specific prosocial behaviors. For example, these studies have demonstrated that the pandemic makes individuals more likely to prioritize society's problems over their own, but less willing to give to non-COVID-19 related causes [37,38]. This interpretation also fits with our finding that Dictator Game giving is higher for COVID-19 related targets.…”
Section: Plos Onesupporting
confidence: 84%
“…Interestingly, recent studies in adults have suggested that during the pandemic there is a shift towards pandemic-specific prosocial behaviors. For example, these studies have demonstrated that the pandemic makes individuals more likely to prioritize society's problems over their own, but less willing to give to non-COVID-19 related causes [37,38]. This interpretation also fits with our finding that Dictator Game giving is higher for COVID-19 related targets.…”
Section: Plos Onesupporting
confidence: 84%
“…As an example about immigration, it is possible that the global nature of the coronavirus emergency might have elicited empathy towards other cultures and other ethnic groups, hence inspiring a more positive feeling towards immigrants. This possibility would be consistent with recent data suggesting that increasing the salience of the coronavirus pandemics makes Americans more willing to prioritize society's problems over the own problems (Cappelen et al, 2020). Alternatively, judgement about immigration might have been guided by considerations that public resources have been employed for the care of immigrants who fell ill, hence leading to a more negative attitude towards immigration.…”
Section: Introductionsupporting
confidence: 69%
“…Another key advantage of our design is that we can match our newly collected data with participants’ responses to an experimentally validated survey measure of prosociality ( Falk et al, 2018 ) collected two years before, in 2018, as part of an independent study. A potential concern is that prosociality may have changed during the COVID-19 outbreak ( Branas-Garza et al, 2020 , Cappelen et al, forthcoming ) and that this change relates to health behaviors. Our pre-pandemic prosociality measure allows us to address this concern.…”
Section: Introductionmentioning
confidence: 99%